PK/PD Modeling to Assess Rifaximin Clinical Dosage in a Mouse Model of Staphylococcus aureus-Induced Mastitis - Wang, Honglei; Chen, Chen; Chen, Xiaojie; Zhang, Jingju; Liu, Yiming; Li, Xiubo (Frontiers in Veterinary Science, 2021)
Staphylococcus aureus (S. aureus) is a common pathogen that causes mastitis, an infection of the milk-secreting tissue of the udder, in dairy cows, and presents a huge economic problem for the dairy industry worldwide. Thus, control and treatment of mastitis in dairy cows is vital in order to reduce the costs associated with the disease. The main purpose of the current work was to examine the current dosage of rifaximin for the treatment mastitis in cows caused by S. aureus using pharmacokinetic/pharmacodynamic integration in a mouse mastitis model. The mouse mastitis model was established via injection of S. aureus Newbould 305 (400 CFU/gland) into the mouse mammary gland. A single dose of 50, 100, 200, or 400 μg/gland, administered via intramammary infusion, was used to study the pharmacokinetics of rifaximin. The pharmacokinetic parameters were analyzed by non-compartment and non-linear mixed-effect models using Phoenix software (version 8.1; Pharsight, USA). In vivo pharmacodynamics was used to examine 18 therapeutic regimens covering various doses ranging from 25 to 800 μg/gland and three dosing intervals of 8, 12, and 24 h per 24 h experiment cycle. The antibacterial effect of rifaximin was elevated with higher concentrations of rifaximin or shorter intervals of administration. The percentage of time that drug concentrations exceeded the MIC during a dose interval (%T > MIC) was generally 100% for rifaximin and was not better than AUC24/MIC in the sigmoid Emax model of inhibitory effect. The optimal antibacterial effect was 2log10CFU/gland when the magnitude of AUC24/MIC reached 14,281.63 h. A total of 14,281.63 h of AUC24/MIC was defined as a target value in the Monte Carlo simulation. The clinically recommended dosage regimen of 100 mg/gland every 8 h in 1 day achieved an 82.97% cure rate for the treatment of bovine mastitis caused by Staphylococcus aureus infection.